A Phenomenological Meditation on Shinya Tsukamoto’s Vital (Existential Analysis: Journal of the Society for Existential Analysis, 2015)
The present paper pays tribute to Shinya Tsukamoto, one of Japan's best known, albeit controversial, filmmakers. To begin with, the author identifies a form of writing called the phenomenological meditation; and claims this unique form of writing as an act of rebellion against intellectual constraints. The author then proceeds to illustrate the phenomenological meditation by means of a description of Shinya Tsukamoto's (2004) film Vital. Tsukamoto's film is thus revealed as a profoundly insightful reflection on the lived body. Finally, the author contrasts the phenomenological meditation with procedural forms of doing phenomenology; and concludes that the phenomenologist's primary task is to awaken a profound sense of wonder in, and reverence for, phenomena.
Keywords: Meditation; Dissection; Objective Thought; Lived Body; Thing-to-be-Dissected; Person-to-be-Loved; Causality; Beyond-the-Natural; Film Phenomenology